Characterization of cannibalism in early paralarvae of Patagonian red octopus, Enteroctopus megalocyathus (Gould, 1852), grown in a controlled environment - Viviana Espinoza; Ana Farías; Iker Uriarte (Journal of the World Aquaculture Society, 2021)
Abstract In the experimental mariculture of Patagonian red octopus, Enteroctopus megalocyathus, paralarvae rearing showed the highest mortalities. Part of this mortality has been attributed to cannibalism, so we studied the joint effect of paralarvae density and prey availability upon cannibalism in the first 2 weeks after hatching. Three culture densities (1, 5, and 10 paralarvae/L) and three prey availabilities (0, 5, and 10 prey day−1 paralarvae−1) were tested. Two experiments were carried out in early paralarvae: one experiment where the prey consisted of artemia 5 mm in size (Experiment 1) and other experiment where the artemia size was 1 mm (Experiment 2). Results showed, in both experiments, that survival and cannibalism during the first 2 weeks after hatching were independent of the paralarvae density and the prey availability. In experiment 1, with artemia 5 mm in size, the mortality attributed to cannibalism decreased when the prey availability was increased, nor was there any effect of the paralarvae density on cannibalism. In experiment 2, with artemia 1 mm in size, the mortality attributed to cannibalism was independent of both factors. So, the cannibalism in early paralarvae could be reduced by increasing the availability of prey if the prey is of an appropriate size.